Potencial de propagación in vitro de 20 musáceas (Musa AA, AAA, AAAB, AAB, ABB) vía organogénesis directa - Saltos Pérez, Wilmer Iván (2017)
IX. SUMMARY The experiment was carried out in the Biotechnology Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo; Located at the geographical coordinates 79º 32 'West longitude and 01º 49' south latitude; at Km 7.5 of the Babahoyo - Montalvo road, in the province of Los Ríos; at 8.0 msnm, with an annual precipitation average of 2329.8 mm; relative humidity 82%; Heliophania of 998.2 light hours and temperature of 25.6 °C. Meristematic apex of 20 species of musaceae AA, AAA, AAAB, ABB, AAB were used. Materials and equipment were used such as test tubes, beaker, flask, micro pipettes, test tubes, lighter, scalpel, scales, sterile paper, scale, agitator plate, ph-meter, distiller, flow chamber, autoclave, stove, refrigerator and reflector. The studied treatments were 20 cultivars of Musaceae such as: Orito, Gran Cavendish, Valery, Gros Michel, Gran Enano, Banano Rojo, Almendra Tailandesa, Guineo Morado, Guineo Enano, Manzano, Cuatro Filos, Tres Filos, FHIA-21, Plátano Enano, Dominico, Barraganete, Enano Hartón, Maqueño, Plátano sin Tora and Limeño. The experiment was set up in a Completely Random Design (DCA) with uneven number of replicates, using the statistical software InfoStat. Statistical analysis for the prediction of plant numbers up to the eighth propagation for each, regression analysis was used. The experiment consisted in inducing and multiplying in vitro 20 accessions. Three propagations were conducted after breaking apical dominance of the explant, and the potential of propagation up to the eighth times was predicted in the species under study. Preparation of stock solutions or stocks and culture media of induction and multiplication, selection of material; extraction and disinfection of corm; extraction of the meristematic apex, planting the meristematic apex in an induction medium and rupture of apical dormancy and multiplication was carried out. The evaluated variables were: Frequency of propagation (Days), Number of explants / propagation / cultivar and Number of shoots / explant / propagation / cultivar. The obtained results it was determining that the cultivar Gran Enano and Banano Rojo reported higher frequency in days up to dormancy breaking both with 38 days, whereas the cultivar Cuatro Filos showed higher frequency in days in the propagation 1 and 2 and Gran Cavendish in the propagation 3. Varieties of banana genotype (AA, AAA) showed an average of 37 days of intervals to perform each subculture. While varieties of the banana genotype (ABB, ABB) showed an average of 25 days and varieties of the banana genotype (AAAB, AAB) showed an average of 23 days.The highest number of explants per propagation was obtained in the cultivar FHIA-21 in propagation number 1, 2 and 3, and even for the predicted values. In relation to the response of multiplication of shoots by genotypes the Banana cultivars (AA, AAA) presented higher shoot multiplication values comparing with the others cultivars. The variance increased progressively to peak 8 and for every 10 shoots of peak 2 there were 18 shoots in the propagation 3.